Optimalisasi Produksi Telur Asin melalui Inovasi Mesin Pencuci Telur Otomatis dan Digitalisasi Manajemen Usaha - Rahma, Rana Ardila; Sugiharto, Muhammad; Debora, Fransisca; Fasa, Nadia; Wahyudin, Wahyudin; Gultom, Louisa Paulina Febriana; Edriawati, Natasya Aksani (Jurnal SOLMA, 2025)
Background: Salted egg production is one of the processed food sectors with strong market potential but still faces efficiency challenges, particularly in the egg washing stage. SMEs Digdo Bintang Telur in North Cikarang, as the partner in this program, still relied on manual washing methods, limiting production capacity to approximately 200 eggs per day and resulting in a high rate of shell damage. This Community Service Program aims to reduce the time and labor required for egg washing, minimize shell damage through the implementation of an automatic salted egg washing machine, and introduce digitalization in bookkeeping and marketing practices. Method: The implementation methods included socialization, training, machine installation, mentoring, evaluation, and the development of digital bookkeeping and online marketing. The implemented machine was equipped with adjustable speed control, cleaning brushes, inspection lighting to assess egg quality, and an automatic counter for clean and qualified eggs. The results showed a significant improvement, with productivity increasing up to sixteenfold and the rate of shell damage decreasing by 69%. Evaluation of digital bookkeeping revealed improved record accuracy, easier transaction tracking, and faster financial summaries through the use of digital applications and QRIS-based payments. In terms of marketing, analysis of social media reach and engagement (Facebook and Instagram) indicated an increase in online purchases of up to ten orders. Conclusion: This program proved effective not only in enhancing productivity through the innovation of an automatic salted egg washing machine but also in strengthening the partner’s competitiveness through bookkeeping and marketing digitalization.